Prevalence of chemsex and associated factors among gay, bisexual, and other men who have sex with men in Nepal: findings from an online national survey - Kiran Paudel; Kamal Gautam; Anjila Pandey; Prashamsa Bhandari; Jefferey A. Wickersham; Manisha Dhakal; Md. Safaet Hossain Sujan; Bibhav Acharya; Sabitri Sapkota; Archana Shrestha; Roman Shrestha (Scientific Reports)
Abstract The increase in the chemsex phenomenon among gay, bisexual, and other men who have sex with men (GBMSM) is alarming, as it is associated with risky sexual behaviors, including condomless sex and multiple sex partners. Despite increasing concerns, there is nonexistent research on chemsex among GBMSM in Nepal. Therefore, our study aimed to identify the prevalence and factors associated with engagement in chemsex among GBMSM in Nepal. A cross-sectional online survey of 842 Nepali GBMSM was conducted between March and May 2024. Multivariable logistic regression was used to identify factors associated with chemsex engagement within the past 12 months. Among 842 participants (mean age 27.6 ± 7.1 years), 24.7% reported ever engaging in chemsex, and 19.1% did so in the past 12 months. GBMSM who had completed high school were less likely to have engaged in chemsex in the past 12 months (aOR: 0.5; 95% CI: 0.3–0.8). However, GBMSM who reported having multiple sex partners (aOR: 9.6; 95% CI: 1.3–71.4), being involved in party/group sex in the past 12 months (aOR: 2.5; 95% CI: 1.5–3.9), and with depressive symptoms (aOR: 2.0; 95% CI: 1.3–3.0) were more likely to have engaged in chemsex in the past 12 months. An integrated approach is urgently needed, encompassing awareness raising, safe drug use support, sexual health services, and mental health care.